Analysis of sales return and economic order quantity to assess turn of goods inventory - Saprudin Saprudin; Sita Dewi; Tiara Hana Pratiwi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Significant developments in the manufacturing and household consumption industries form the background of this study. Analyzing the impact of sales return, EOQ (Economic Order Quantity) on the turnover of goods is the aim of this study. This study takes the sample of PT Informa Furnishing - Kota Kasablanka Mall, through financial statement data and related reports from 2015 to 2018, as well as interviews with company management. The results of this study illustrate that sales return also affects inventory turnover, Economic Order Quantity can also affect inventory turnover through the accuracy of the number of purchases of goods. Thus the management needs to maintain the quality of goods so that sales return can be minimized and must maintain the ideal amount of purchase of goods so that inventory is well maintained, and inventory turnover runs quickly.